From Operation Warp Speed to TRIPS. Vaccines as Assets - Tatiana Andersen (Covid-19 and the Global Political Economy. Crises in the 21st Century, 2022)
This chapter examines the political economy of biopharmaceutical innovation, focusing primarily on vaccines in the Covid-19 pandemic. This analysis aims to make visible the deep entanglements that entrench an extractive and dysfunctional innovation ecosystem, calcifying inequities in global access to essential medicines. The chapter argues that the current inequities in vaccine access are not new or anomalous and that they are the result of a complex yet strategic enmeshment among the logics of war and biomedicine, asset accumulation, and intellectual property. Uneven access to Covid-19 therapeutics can be traced to these three elements, which have built inequity into the political economy of biomedicine long before the current pandemic. The first section in the chapter teases out the first entanglement by unpacking Operation Warp Speed (OWS) as the culmination of a historical war-biomedical nexus driven by the United States, which has important implications for the global political economy of biomedical innovation and North-South asymmetries. The second section places OWS in the broader context of an extractive innovation ecosystem guided by a logic of differential accumulation characterised by the assetisation of publicly funded research. The final section explores how asset accumulation logics and unequal access to therapeutics are embedded in the international architecture of the Intellectual Property Rights (IPRs) regime.
Keywords: P16; P26; O3; P14; 330; biomedicine; bio-pharmacology; covid-19; differential accumulation; dominant capital; intellectual property; sabotage; technology